The determination of bread dough readiness during kneading of wheat flour: A review of the available methods. (November 2021) - Parenti, Ottavia; Guerrini, Lorenzo; Mompin, Sara Bossa; Toldrà, Mònica; Zanoni, Bruno
Abstract: Kneading is one of the most important steps in the bread-making process of wheat flour. The quality of wheat breads mostly depends on the proper development of the gluten network, making the measurement of dough readiness or development a key processing factor. This paper provides a review of both standard and alternative methods of measuring bread dough readiness. Although optimum dough development is commonly measured using descriptive rheological tests (i.e., Farinograph and Mixograph tests), the reference methods showed several limits, resulting in a poor correlation with bread quality. Some alternative methods were proposed for a more accurate determination of bread dough readiness and their potentiality is discussed as a function of the field of application. However, the scant information about alternative methods reported in the literature outlines the necessity to encourage further investigations on this topic. Highlights: Key role of the kneading step for the correct development of bread dough structure. Bread dough readiness represents the optimal dough development during kneading. Review of all the available methods to determine bread dough readiness. Discussion of strengths and weaknesses of the methods for dough readiness. Evaluation of the potential applicability of the methods to improve process control.